PENERAPAN KETERAMPILAN BERPIKIR KRITIS DALAM PERKULIAHAN FISIKA MODERN - Silangen, Patricia Mardiana (Program Studi Pendidikan Fisika Jurusan Fisika Fakultas Matematika, Ilmu Pengetahuan Alam, dan Kebumian (FMIPAK), Universitas Negeri Manado, 2024)
This study aims to evaluate the implementation of critical thinking skills in Modern Physics study among students of the Physics Education Program at Universitas Negeri Manado.This method used a quantitative approach with a one-group pretest-posttest design. There were 9 students of third - semester participated and the data were collected using an essay test consisting 5 questions designed to measure critical thinking skills. Data analysis was conducted using descriptive and inferential statistics to assess the improvement in pretest and posttest scores. The results showed a significant improvement in students' critical thinking skills. The average pretest score of 16.89% increased to 73.56% in the posttest. Statistical analysis showed a significant difference with a p-value < 0.05, indicating that the instructional intervention was effective. Students demonstrated progress in their ability to analyze problems, interpret data, and draw logical conclusions based on evidence. These findings highlight the importance of integrating critical thinking skills into Modern Physics teaching to enhance learning outcomes and students’ analytical abilities.